2002
DOI: 10.1254/jjp.89.7
|View full text |Cite
|
Sign up to set email alerts
|

Research and Development of Donepezil Hydrochloride, a New Type of Acetylcholinesterase Inhibitor

Abstract: ABSTRACT-A wide range of evidence shows that cholinesterase (ChE) inhibitors can interfere with the progression of Alzheimer's disease (AD). The earliest known ChE inhibitors, namely, physostigmine and tacrine, showed modest improvement in the cognitive function of AD patients. However, clinical studies show that physostigmine has poor oral activity, brain penetration and pharmacokinetic parameters, while tacrine has hepatotoxic liability. Studies were then focused on finding a new type of acetylcholinesterase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
129
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(140 citation statements)
references
References 53 publications
4
129
1
4
Order By: Relevance
“…In order to determine whether a potentiating effect on the ASR (and a delayed habituation response) could also be achieved with other agents linked to memory enhancing effects, donepezil and memantine were evaluated in the assay since they act through different pharmacological mechanisms, donepezil being an acetylcholinesterase inhibitor (Sugimoto et al, 2002) and memantine an NMDA receptor antagonist (Parsons et al, 1999). Both are current therapies for Alzheimer's disease and have been shown to improve cognitive ability in Alzheimer's disease patients (Burns et al, 1999;Winblad et al, 2001Winblad et al, , 2006Peskind et al, 2006;Takeda et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine whether a potentiating effect on the ASR (and a delayed habituation response) could also be achieved with other agents linked to memory enhancing effects, donepezil and memantine were evaluated in the assay since they act through different pharmacological mechanisms, donepezil being an acetylcholinesterase inhibitor (Sugimoto et al, 2002) and memantine an NMDA receptor antagonist (Parsons et al, 1999). Both are current therapies for Alzheimer's disease and have been shown to improve cognitive ability in Alzheimer's disease patients (Burns et al, 1999;Winblad et al, 2001Winblad et al, , 2006Peskind et al, 2006;Takeda et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Cholinergic neurons degenerate in patients with Alzheimer's disease as well as senile dementia, and, importantly, the degree of degeneration highly correlates with functional loss in these disorders (Davies and Maloney, 1976;Perry et al, 1978a, b). Clinical trials revealed that donepezil (Aricept, previously E2020, Pfizer), a selective noncompetitive inhibitor of acetylcholinesterase (AChE; see Sugimoto et al (2002) for a review), had cognitive benefits in Alzheimer's disease patients afflicted with mild to moderate degrees of dementia (Mintzer and Kershaw, 2003). Presently donepezil is used to treat cognitive deficits associated with Alzheimer's disease (Rogers and Friedhoff, 1998;Doody, 1999;Grutzendler and Morris, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is useful for prevention and treatment of Alzheimer's disease by virtue of its acetyl cholinesterase inhibitory action 22 . There are many processes described mainly in patent literature [23][24][25][26][27][28][29][30][31][32] for producing (4) and its pharmaceutically acceptable salts. Complete chemo-selectivity is unlikely, because the starting compound (1) has more than one functionality susceptible to hydrogenation.…”
Section: Introductionmentioning
confidence: 99%